Belief in a just world and secondary victimization : The role of adolescent deviant behavior - Mendonça, Rita Duarte (2016)
Belief in a Just World research found evidence that one feels threatened whenever one witnesses an innocent victim suffering, often resorting to secondary victimization to neutralize the observed injustice. However, literature has neglected the explanatory power of adolescent deviant behavior in victimization processes. This study (n = 284 students) aims to determine the impact of the adolescents' deviant behavior, BJW and victim's innocence on secondary victimization. Additionally, we analyzed juvenile deviant behavior's impact on victim identification. Juveniles who committed more deviant behaviors identified less with the victim than those with lower deviance levels. The interaction effects show that juveniles who are strong just world believers and have higher delinquency engaged significantly more in secondary victimization when confronted with an innocent victim. These results clarify the role played by adolescent deviant behavior and BJW in secondary victimization judgments regarding situations with innocent and non-innocent victims.